Monocyte chemoattractant protein-1 in patients with peripheral arterial disease - Jana Petrkova; Jaroslava Szotkowska; Zuzana Hermanova; Jan Lukl; Martin Petrek (Mediators of Inflammation)
Background: Chemokine-driven migration of inflammatory cells has been implicated in the pathogenesis of atherosclerotic conditions including peripheral arterial disease (PAD). Monocyte chemoattractant protein-1 (MCP-1) is elevated in patients with coronary artery disease and in hypertensive patients. This study therefore investigated MCP-1 in patients with PAD.